A bibliometric review on vitamins and Alzheimer’s disease between 1996 and 2023 - Sun, Xiaoyu; Xu, Haichun; Qu, Huiling; Dong, Wenwu (Frontiers in Aging Neuroscience, 2023)
Objective Alzheimer’s disease (AD) is a major disease that affects the elderly worldwide. Several studies have revealed that vitamins may influence the risk of developing AD. However, information in this field remains ambiguous. Therefore, this study aimed to examine the relationship between AD and vitamins, identify journal publications and collaborators, and analyze keywords and research trends using a bibliometric method. Methods We systematically searched the Web of Science (WOS) Core Collection for papers published on AD and vitamins. Retrieved data regarding institutions, journals, countries, authors, journal distribution, keywords, and so on. SPSS 25 software was used for the statistical analysis, and CiteSpace V.6.1.R6 was used to visualize the information through collaborative networks. Results A total of 2,838 publications were ultimately included in accordance with the specified inclusion criteria. The number of publications gradually increased from 1996 to 2023, with papers published in 87 countries/regions and 329 institutions. China (centrality: 0.02) and the University of Kentucky (centrality: 0.09) were the major research countries and institutions, respectively. NEUROLOGY was cited most frequently, reaching 1,573, and had the greatest impact. The cited keywords show that “Alzheimer’s disease,” “oxidative stress,” “vitamin E,” and “dementia” have been research hotspots in recent years. Beta-carotene emerged in 2023 and was identified as a developmental trend in this field. Conclusion This is the first bibliometric analysis of vitamins associated with AD. We identified 2,838 articles in the field of vitamins and AD, analyzed the information of major countries/regions, institutions, and core journals in this field, and summarized the research hotspots and frontiers. These findings provide useful information for researchers to explore the role of vitamins in AD further.